Pendidikan Karakter Anak Usia Dini Melalui Kegiatan Kepramukaan Di SDN Karanggintung 01 Dan SDN Karanggintung 02 Kecamatan Gandrungmangu - Rama Cipta Prasetia; Kuat Leksono; Alwi Fauji (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This scouting activity will go through several stages until in the end the students receive the character education referred to by the author. The first stage is basic, namely an introduction to the history of